Marketplace Design With Joomla Case Study: PT. Lum Cengkareng - Firdaus, Mohamad (Pt. Anagata Sembagi Education, 2024)
Online marketplaces are so mushrooming that it can make it easier for someone to transact in everyday life. With this technology, market penetration is increasingly widespread and can generate large business profits. A company located in the Cengkareng area of West Jakarta is trying to develop its business. In accelerating the development of their business they are trying to organize a design and creation of an online marketplace and also provide training on the use of features in the marketplace online that can be used by the community to make transactions quickly. The method used in making this design is an explorative method in the application life cycle, where a marketplace website will be designed with the Content Management System application. The results of this paper show that the design of a marketplace website can be built using the CMS application, namely Joomla. This research is a form of utilization of online-based information technology at PT LUM.